PENYULUHAN TENTANG PENTINGNYA IMUNISASI PADA BAYI DI POSYANDU KASIH IBU DI DESA PELAWAN KECAMATAN PELAWAN KABUPATEN SAROLANGUN - Safitri Safitri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Immunization protects children against some diseases that can be prevented by immunization (PD3I). Every year more than 1.4 million children in the world die from various diseases that can actually be prevented by immunization. Although in reality there are now many mothers who bring their babies to medical personnel to get immunization, only a small of them are given counseling. In Pelawan Village 44.37% of toddler did not get complete basic immunization, the reason they lacked knowledge of 42.86% and busy 57.1%. .Target outcomes expected are: there is an increased knowledge an increase in knowledge between before and after counseling, and awareness of mothers to bring their children to Posyandu to get immunization. The method used is counseling. The results of dedication are an increase in knowledge and awareness of mothers to bring their children to get immunizations in an effort to prevent disease.